All Days 2011
DOI: 10.2118/146058-ms
|View full text |Cite
|
Sign up to set email alerts
|

Superior Quality Diamond Heel Inserts Improve Cutting Structure and Seal Life in Abrasive and Directional Applications

Abstract: Polycrystalline diamond compact (PDC) bit technology and the application of PDC bits continues to improve and consequently, the window of application for roller-cone bits is being narrowed. This paper will demonstrate how in this narrowed window of tougher application focus, operators can gain additional performance and economic benefits by employing the latest design methods and materials including a new generation of diamond enhanced inserts.The primary applications of focus where roller-cone bits are still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Further, they concluded that the TiAlSi coated drill bits showed better performance and achieved the lowest wear rate in comparison to DLC-Diamond coating and Tungsten Carbide (WC) coated drill bits. Interestingly, a new technology of Diamond Enhanced Inserts (DEI) showed improved resistance to bit wear during abrasive drilling conditions 74 .…”
Section: The Role Of Coatings In Drilling Applicationsmentioning
confidence: 99%
“…Further, they concluded that the TiAlSi coated drill bits showed better performance and achieved the lowest wear rate in comparison to DLC-Diamond coating and Tungsten Carbide (WC) coated drill bits. Interestingly, a new technology of Diamond Enhanced Inserts (DEI) showed improved resistance to bit wear during abrasive drilling conditions 74 .…”
Section: The Role Of Coatings In Drilling Applicationsmentioning
confidence: 99%